An Unusual Case of Gastrointestinal Bleeding from Isolated Gallbladder Varices in a Patient with Pancreatic Cancer Complicated by Portal Biliopathy - Mahir Gachabayov; Kubach Kubachev; Elbrus Abdullaev; Nonna Zarkua; Abakar Abdullaev; Artur Fokin (Case Reports in Gastrointestinal Medicine)
Portal biliopathy is the complex of abnormalities of extrahepatic and intrahepatic bile ducts, cystic duct, and gallbladder, arising as a result of extrahepatic portal vein obstruction and noncirrhotic portal fibrosis, which can be caused by coagulopathies, tumors, inflammation, postoperative complications, dehydration, and neonatal umbilical vein catheterization. We report a case of a 55-year-old male patient with the history of pancreatic cancer and cholecystoenteric anastomosis presenting with gastrointestinal bleeding from gallbladder varices via the anastomosis.